Impacts of the COVID-19 pandemic on ginger production: Supply chains, labor, and food security in Northeast Thailand - Wannaprasert, Pakhuan; Choenkwan, Sukanlaya (Forest and Society, 2021)
This paper evaluates the impacts of the COVID-19 pandemic on ginger production and ginger farmer livelihoods in Loei province where ginger is an important commercial crop. The analysis also pays particular attention to the lockdown period (March – June 2020). Data for this study were obtained from several sources, including information from government records, onsite observation, and semi-structured interviews. Field research was conducted in August 2020 for 10 days in a village in Plaba sub-district. Data was obtained using an interview guide with 55 ginger farmers who have been growing ginger for at least 3 years. The results show that the lock down and transportation restrictions affected input supply chains, such as fertilizer and rhizome seeds. The flow of international labor was also constrained affecting skilled labor shortage in ginger production. However, COVID-19 shows positive impacts on ginger production systems. Ginger price is higher than the previous year because of world market demand and the belief that ginger can be used as an antioxidant to prevent COVID-19 infections. Moreover, the result also shows that these ginger farmers are somewhat resilient in the face of COVID-19 as they are not much dependent on markets for their own subsistence needs. Finally, this study recommends that promoting farmers to produce their own food and diversify commercial crops would be a good strategy for farmers to survive the crisis.